Functional Thenar Reconstruction: A Case Report and Systematic Review of the Literature. Issue 6 (December 2022) - Tadisina, Kashyap K.; Kareh, Aurora M.; Hasan, Samir; Frojo, Gianfranco; Xu, Kyle Y.
Abstract: Reconstruction of the thumb is among the most complex challenges faced by hand surgeons. Meaningful functional recovery of the thumb is dependent mainly on thumb opposition and palmar abduction. Free functional muscle transfer provides neurotized, robust soft tissue coverage that can achieve dynamic reconstruction of thenar musculature in a single stage. We present a case of a free neurotized segmental gracilis muscle transfer for thenar reconstruction and a systematic review of thenar reconstruction with free functional muscle transfer in the literature. A teenage male patient with a gunshot-induced thenar defect was reconstructed using a free neurotized gracilis muscle measuring 5 × 11 cm. The obturator nerve was coapted to the recurrent motor branch of the median nerve. The patient reached M4 strength at 10 months with functional use of his thumb. A systematic review of options for functional thenar reconstruction revealed 14 studies describing functional thenar reconstruction in 44 patients. Successful functional flaps described included gracilis muscle, pronator quadratus muscle, pectoralis minor muscle, abductor hallucis muscle, extensor digitorum brevis muscle, and serratus anterior muscle. Microsurgical transfer of a functional muscle is an excellent option for single-stage thenar reconstruction of both form and function. There are a number of available donor sites with equivalent size and bulk to that of native thenar musculature.